The Contemplative Life of the Spirituality of OCSO Monks in Documentary Photography - Fransiskus Xaverius Guritno (Indonesian Journal of Visual Culture, Design, and Cinema, 2025)
The Contemplative Life of OCSO Monks' Spirituality in Documentary Photography at the Santa Maria Rawaseneng Monastery is a unique and complex spiritual journey that reflects individual transformation through experience, reflection, and change. This research aims to explore and delve into the spiritual aspects experienced by the monks, as well as how they embody the vows that form the foundation of their lives: celibacy, poverty, and obedience. The methodology used in this study is a qualitative approach with documentary photography techniques, which allows the researcher to capture important moments in the daily lives of the monks. The findings indicate that contemplative life involves not only practices of worship and prayer but also interactions with the community and manual labor, which are integral parts of their spirituality. Through careful image capture, this research successfully reflects the spiritual values and daily lives of the monks, as well as the challenges they face in living a cloistered monastic life. The conclusion of this study emphasizes that contemplative spirituality is a journey that encompasses all aspects of life, where the monks strive to achieve unity with God through every activity they undertake.f